Lessons Learned from Applying Human Computer Interaction (HCI) Techniques to the Redesign of a User Interface - Yin, Karen Lee Choy (Universiti Teknologi Petronas, 2004)
This research details the finding on web page design principles focusing on the Human Computer Interaction (HCI) aspect. The focus was derived from the Top Ten (10) Web Page Design Mistakes (2003) by Jakob Nielsen, a well-known guru of HCI and usability. In this technological era, there are thousands and millions of web sites and pages but how many of these pages are properly designed? Web page designers nowadays focus too much on the functionality of a system instead interface design which actually projects an application's uniqueness and key messages that creates the desired emotional response from the users involved The objectives of this research includes investigation of principles applied in HCI for web page interface design, redefinition of the erroneous web pages and formulation of domain-specific rules to ensure the effectiveness, practicality and acceptance of these techniques. Usability lab testing, questionnaires, prototype screens are done to focus on evaluation, based on the usability criteria of web pages identified from many credible sources. This research was done based on the fact that Internet users' preference and ease of browsing plays a vital role in deciding the acceptance of a web page. A powerful system would be left behind by users if it is not user friendly or designed according to the standards, principles and guidelines of HCI. The methodology used concentrates on a problem-specified framework which was developed by the author. There were six (6) processes involved namely Identification of target users, User consultation, Task analysis, Usability and accessibility assurance, Consideration of web design issues and Formulation of user interface design specification. The final result of this study is a domain specific guideline of HCI for web page design customized for profit making organizations and individuals. In conclusion, HCI principles is inseparable when it comes to web designing issues and this will continue to be vital as long as web page exist and is used by many.